2001
DOI: 10.1021/bi010942w
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Gramicidins A, B, and C Incorporated into Sodium Dodecyl Sulfate Micelles,

Abstract: Gramicidins A, B, and C are the three most abundant, naturally occurring analogues of this family of channel-forming antibiotic. GB and GC differ from the parent pentadecapeptide, GA, by single residue mutations, W11F and W11Y, respectively. Although these mutations occur in the cation binding region of the channel, they do not affect monovalent cation specificity, but are known to alter cation-binding affinities, thermodynamic parameters of cation binding, conductance and the activation energy for ion transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
212
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(222 citation statements)
references
References 57 publications
8
212
0
1
Order By: Relevance
“…Each gA subunit has four Trps, which in the singlestranded (SS) ␤-helical channel structure are localized near the membrane/water interface ( Fig. 1C) (22,23). Changing the membrane environment (24,25) or the amino acid sequence (18,19,26) can alter the gA folding preference, in some cases promoting the folding into double-stranded (DS) dimeric structures (Fig.…”
mentioning
confidence: 99%
“…Each gA subunit has four Trps, which in the singlestranded (SS) ␤-helical channel structure are localized near the membrane/water interface ( Fig. 1C) (22,23). Changing the membrane environment (24,25) or the amino acid sequence (18,19,26) can alter the gA folding preference, in some cases promoting the folding into double-stranded (DS) dimeric structures (Fig.…”
mentioning
confidence: 99%
“…3B). Tryptophan, with an indole side chain bearing both hydrophobic and hydrophilic properties, is the most representative amino acid with an inherent membrane interaction ability, and it often plays an important role by anchoring proteins within the lipid bilayer (41)(42)(43)(44)(45).…”
mentioning
confidence: 99%
“…Tryptophanyl Substitution of GGN5 N11 -Tryptophan has been rarely found in natural antimicrobial peptides with amphipathic helical structures, although some antimicrobial peptides in different structural groups are particularly rich in tryptophan (42)(43)(44)(45). Recently, we found that a single tryptophanyl substitution at position 16 in the ⌬ 24 -37 GGN4 (or GGN4 N23 ), a synthetic, inactive fragment of gaegurin 4 (GGN4), generated strong antimicrobial activity without significant hemolytic activity (21,34).…”
mentioning
confidence: 99%
“…This phenomenon can be observed in gramicidin A, for example, in which axial self-recognition takes place in the membrane environment. [32] In peptidic foldamers, axial helix-helix interactions were recently observed in the self-association of the β-peptidic H12 helix to form the large-diameter β-H18 helix. [33] In this work we report on the serendipitous discovery of the largest-diameter β-peptidic mixed helix known to date, the β-H18/20 helix, the formation of which is solventdependent and its folding occurs cooperatively through head-to-tail interactions in solution.…”
Section: Introductionmentioning
confidence: 99%